2019
DOI: 10.18805/ijar.b-3760
|View full text |Cite
|
Sign up to set email alerts
|

Accessing drop in milk production in cattle due to cold climate and subsequent nutrient amelioration in temperate Kashmir

Abstract: The preliminary study to quantify the drop in milk production in cattle due to cold climate and subsequent nutritional amelioration in temperate Kashmir where the temperature in the winter months ranges from -4 to 10 0C was conducted at Mountain Live stock Research Institute (MLRI), SKUAST-Kashmir and in various dairy farms in the vicinity. In the treatment group, the animals were provided with 150 grams of jaggery and 200 grams of crushed fenugreek daily in addition to normal feeding schedule. The data regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This may be indicative of poor nutrition to the herd, presence of reproductive diseases, low fertility of the bull or mating of genetic relatives in the herd. Meanwhile the weaning age of 5-7 months (155-217 days) reported in this study is still within the range of 30 days and 231 days reported by (Aarif et al, 2019) and Myers et al, (1999a) respectively. Bottle-fed calves could be weaned at one month of age, while nursed cows could be weaned between ages 3 to 8 months (Filley, 2011;Getahun et al, 2020).…”
Section: Weaning Percentage Of Cattlesupporting
confidence: 83%
See 1 more Smart Citation
“…This may be indicative of poor nutrition to the herd, presence of reproductive diseases, low fertility of the bull or mating of genetic relatives in the herd. Meanwhile the weaning age of 5-7 months (155-217 days) reported in this study is still within the range of 30 days and 231 days reported by (Aarif et al, 2019) and Myers et al, (1999a) respectively. Bottle-fed calves could be weaned at one month of age, while nursed cows could be weaned between ages 3 to 8 months (Filley, 2011;Getahun et al, 2020).…”
Section: Weaning Percentage Of Cattlesupporting
confidence: 83%
“…This could be due to targeting of the right season for calving when enough pasture and veld is available for the cows to produce quality milk for the calves, as well as other variables being constant; resulting in high weaning percentage that could be within 60-100% in Mpumalanga province of South Africa. Calving percentage gives an estimate of the farrowed calves carried to term relative to the total number of females exposed to males during mating season (Aarif et al, 2019;Reiling, 2011). This does not take cognizance of whether the calf was born alive or dead, so long as it was carried to term.…”
Section: Weaning Percentage Of Cattlementioning
confidence: 99%
“…To overcome this problem, jaggery with vitamin C and vitamin C plus electrolytes was evaluated by different researchers on the goat model (Ahmad Mir et al, 2019;Ayari et al, 2018;Gupta et al, 2019Gupta et al, , 2021. In all studies, the result showed a reduction of transportation stress by jaggery with vitamin C and vitamin C plus electrolytes in the experimental goat model (Ahmad Mir et al, 2019;Ayari et al, 2018;Gupta et al, 2019Gupta et al, , 2021, while, jaggery along with fenugreek helps in increased milk production in cattle even in winter months (Aarif et al, 2019). Recently, a research group from China reported jaggery as a potential carbon source and its impact on water quality, growth performance, serum bactericidal capacity, innate immunity, and disease resistance to Aeromonas hydrophila in Orechromis niloticus (Elayaraja et al, 2020).…”
Section: Other Biological Propertiesmentioning
confidence: 99%